2012
DOI: 10.1539/joh.11-0197-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Effort‐reward Imbalance Questionnaire in Greek: Translation, Validation and Psychometric Properties in Health Professionals

Abstract: 119Pavlos MSAOUEL, et al.: Validation of the Greek ERI Questionnaire vals 1.39 to 8.38, p=0.007, respectively). Conclusions:The translated and adapted Greek version is comparable with the original ERI instrument in terms of validity and factorial structure and is suitable for assessment of the psychosocial work environment of Greek healthcare professionals. . The effort-reward imbalance (ERI) model 2) , which focuses on the lack of social reciprocity and fairness between efforts spent and rewards received at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
(53 reference statements)
4
14
1
6
Order By: Relevance
“…In addition, item ERI 15 was among the lowest in factor loadings and correlation item/ total scale in most Latin American samples in the current study, particularly in Argentina and Peru. Previous studies in Greece have also shown that item 15 had the lowest internal consistency [Msaouel et al, 2012]. Overcommitment was the only scale that worked well in all samples, in single and multigroup analyses.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In addition, item ERI 15 was among the lowest in factor loadings and correlation item/ total scale in most Latin American samples in the current study, particularly in Argentina and Peru. Previous studies in Greece have also shown that item 15 had the lowest internal consistency [Msaouel et al, 2012]. Overcommitment was the only scale that worked well in all samples, in single and multigroup analyses.…”
Section: Discussionsupporting
confidence: 49%
“…However, item OV 3 was problematic both in the global sample and in each sub-sample ("When I get home, I can easily relax and switch off work"). This lowest psychometric performance was similar in different ERIQ versions, such as the Greek (R€ odel et al, 2004;Msaouel et al, 2012), Thai [Buapetch et al, 2008] and Italian [Magnavita et al, 2012]. A possible explanation is that this is the only item that needs to be reversely coded before a total score of the overcommitment scale can be obtained, assuming that relaxing at home is exactly the opposite of being overcommitted to work.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This latter distinction is important, since a broader approach may be needed to address these issues if they are common features of a hospital or health care system. The ER ratios returned from this study exceed those seen in many recent international studies of health care staff such as those conducted in China, Mongolia, Germany and France, with only Greek health care workers exceeding our values [24,25]. The mean over-commitment scores were similar to those of other European health care and public sector workers.…”
Section: Discussionsupporting
confidence: 55%
“…Další validizaci řecké varianty ERI-S udělali Msaouel et al (2012). Provedli výzkum na populaci 600 řeckých zdravotníků (lékaři, sestry, fyzioterapeuti, laboranti).…”
Section: Nová Zkrácená Verze Dotazníkuunclassified